Intercultural sensitivity as a mediator in the relationship between implicit intercultural identification and emotional disturbance—An exploratory study of international high school students - He, Jiayin; Song, Xiaoqi; Wang, Chanyu; Zhang, Ruibin (Frontiers in Psychiatry, 2023)
Background Intercultural adaptation always connects with emotional disturbances while implicit intercultural identification and intercultural sensitivity, as different perspectives of intercultural communication competence, are protective to mental health. Little is known about intercultural adaptation and emotional disturbances of new students in international high schools due to the lack of relevant research. Objective We aimed to investigate the prevalence of emotional disturbances on new students in international high schools and confirm the relationship among intercultural identification, intercultural sensitivity and emotional disturbances. Methods Study 1 was an investigation on prevalence of emotional disturbances of 105 senior-one students from an international high school by Self-rating Depression Scale and Self-rating Anxiety Scale. 34 students were invited to study 2 to further explore the relationship between intercultural sensitivity, implicit intercultural identification and emotional disturbances by Intercultural Sensitivity Scale and Single Category Implicit Association procedure. Results Study 1 indicated 15.24% and 10.48% students were disturbed by apparent depression and anxiety symptoms respectively. Study 2 revealed emotional disturbances significantly correlated with intercultural sensitivity (p<0.01) and implicit intercultural identification (p<0.01). While openness factor from intercultural sensitivity mediated on the relationship between implicit intercultural identification and depression symptoms (ratio of indirect effect=41.04%, p<0.05) as well as anxiety symptoms (ratio of indirect effect=34.65%, p<0.05) respectively. Conclusions Present study revealed partially senior-one students of international high school were disturbed by emotional problems while intercultural communication competence was protective. Enhancing international communication competence of senior-one students in international high school is significant.